Determination of the Optimum Conditions for Hexavalent Chromium Removal Using Nano-Aluminum Ferrihydrite - أريج عدرة; إبراهيم راهب; دينا كوسة خليل (Latakia University Journal -Basic Sciences Series, 2022)
In this research, aluminum ferrihydrite , Al/Fe=0.3, was prepared in the laboratory, in addition to studying the optimal conditions for removing hexa-chromium from aqueous solutions (contact time, pH, dose, competitor ion effect), the adsorption isotherm and adsorption model were studied. The results showed that the equilibrium occurred at a contact time of 5 hours and the appropriate pH for adsorption was pH =5-6 where at this value the surface of the ferrihydrite is positively charged and this is suitable for chromate adsorption.the percentage of chromium removal was من68%% ,50.71, 32.8% at conscentrations (100,250,500) ppm straight. The results of the obstructed anion study also showed that the presence of the phosphate moiety hinders the removal of chromates. The data resulting from the adsorption curves were processed according to Langmuir and Freundlich models, and it was found that the adsorption process occurs in a monolayer according to Langmuir.